Analyzing the relationship between traditional ratios and profitability: Airasia Berhad (2005-2015) / Hefa Abdul Aziz - Aziz, Hefa Abdul (Faculty of Business Management, 2017)
This research is for analyzing the relationship between traditional ratios and profitability performance of Malaysian Airline Company: AirAsia Berhad. Airline industry is selected for this research due to the instability earning performance faced by them. The secondary data from Data Stream and published financial report of AirAsia Berhad are taken into consideration to form the financial analysis line. In this paper, quarterly samples of data are taken over 11 years is collected. A time series model is developed to evaluate a complex and statistically the relationship between traditional ratio and profitability performance for this airline company. The relationship between traditional ratio and profitability performance of Airline Company is evaluated based on some selected ratios: Operating Profit Margin (OPM), Net Profit Margin (NPM) and Return on Assets (ROA) are chosen as the profitability rates while Current Ratio (CR), Debt Ratio (DR), and Total Assets Turnover Rate (TATR) are chosen as a traditional financial ratio. Based on regression result, it shows that on the p-value for the F-test statistic denoted by “Prob(F-statistic)” among three dependent variables only Operating Profit Margin variable can reject the null hypothesis at 5% significance level. It indicates that at least one of the independent variables is useful in predicting Operating Profit Margin. Other than that, it can be conclude that only Current Ratio and Total Assets Turnover Rate should be retained in the Operating Profit Margin regression model and Debt Ratio can be dropped. In additional, the other regression model should be dropped because the independent variables are not useful in predicting Net Profit Margin variable and Return on Assets variable.